2007
DOI: 10.1590/s0103-64402007000300008
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Aggregatibacter actinomycetemcomitans between Brazilian women with severe chronic periodontitis and their children

Abstract: This study evaluated the transmission of Aggregatibacter actinomycetemcomitans (Aa) in women with severe chronic periodontitis and their children. Thirty women (mean age = 36.1±6.0 years) who were mothers of at least one child aged 7 to 16 years were enrolled. In order to investigate mother-child transmission of Aa, the children were also evaluated when their mothers were colonized by the bacterium. Subgingival plaque samples of each woman were collected from 3 sites (mean probing depth of 7.3±1.2 mm and mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Two studies reported detection rates by culture of 30-60% in children of adult periodontitis patient, and the genotypes of the strains were always identical [111,112]. A smaller study from Brazil of women with severe chronic periodontitis did not corroborate this finding, as the two culture-positive children carried genotypes that were different from those of their mothers [113]. Horizontal transmission of A. actinomycetemcomitans can occur, and transmission rates between 14% and 60% between spouses have been estimated [18,114].…”
Section: Prevalence and Clinical Significancementioning
confidence: 99%
“…Two studies reported detection rates by culture of 30-60% in children of adult periodontitis patient, and the genotypes of the strains were always identical [111,112]. A smaller study from Brazil of women with severe chronic periodontitis did not corroborate this finding, as the two culture-positive children carried genotypes that were different from those of their mothers [113]. Horizontal transmission of A. actinomycetemcomitans can occur, and transmission rates between 14% and 60% between spouses have been estimated [18,114].…”
Section: Prevalence and Clinical Significancementioning
confidence: 99%
“…2 Aggregatibacter actinomycetemcomitans is an immobile microaerophilic, facultative anaerobic, gram negative coccoid rod, 3 strongly associated with pathogenesis of periodontal diseases, particularly aggressive generalized periodontitis. 4 Some of this bacterium's membranous proteins play an important role in attachment to and penetration in tissue cells. 5 Other virulence factors secreted by this bacterium include an agent that inhibits the reproduction of fibroblasts and a leukotoxin that kills the leukocytes.…”
Section: Introductionmentioning
confidence: 99%
“…[2729] Our values are similar to the frequencies reported, using culture techniques (26.6%; 26.3%) and polymerase chain reaction (PCR) (23.6%) in South Americans populations. [243031] A. actinomycetemcomitans has ability to survive and colonize periodontal pockets probably related to its large scope of virulence factors that include proteolytic activity, capacity of modulate immune response, evasion of phagocytosis, ability to evade, and damage the immune system and produce periodontal breakdown. [32] Some previously published studies even demonstrated that A. actinomycetemcomitans is a pathogen which is able to invade periodontal tissues, but evade mechanical-chemical therapies.…”
Section: Discussionmentioning
confidence: 99%